Pelayanan Kesehatan Pada Ibu Hamil Dengan Risiko Tinggi: Systematic Review - Marissa, Febi; Kusumawaty, Ira (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2023)
Background: One of the efforts to support the acceleration of the decline in maternal mortality and neonatal mortality is to optimize the handling of obstetrics and neonatal emergencies/complications at the basic service level through the Basic Neonatal Emergency Obstetrics Service (PONED). The purpose is to see about health services in pregnant women with high risk. This article uses a systematic review approach Methods: Articles were searched through electronic databases systematically in ScienceDirect and PubMed using the keywords (((((('Obstetrics) OR (''Essential)) And (